Effects of Material–Tissue Interactions on Bone Regeneration Outcomes Using Baghdadite Implants in a Large Animal Model. Issue 15 (6th June 2018) - Li, Jiao Jiao; Akey, Austin; Dunstan, Colin R.; Vielreicher, Martin; Friedrich, Oliver; Bell, David C.; Zreiqat, Hala
Abstract: Extensive bone loss due to trauma or disease leads to impaired healing. Current bone grafts and substitutes have major drawbacks that limit their effectiveness for treating large bone defects. A number of bone substitutes in development are undergoing preclinical testing, but few studies specifically investigate the in vivo material–tissue interactions that provide an important indicator to long‐term implant safety and efficacy. This study is the first of its kind to specifically investigate in vivo material–tissue interactions at the bone–implant interface. Baghdadite scaffolds implanted in critical‐sized segmental defects in sheep tibia for 26 weeks are analyzed by focused ion beam scanning electron microscopy, multiphoton microscopy, and histology. The scaffolds are seen to induce extensive bone formation that directly abut the implant surfaces with no evidence of chronic inflammation or fibrous capsule formation. Bone remodeling is influenced by slow in vivo degradation around and within the implant, causing portions of the implant to be incorporated into the newly formed bone. These findings have important implications for predicting the long‐term effects of baghdadite ceramics in promoting defect healing, and support the translation of baghdadite scaffolds as a new generation of bone graft substitutes with improved properties for the repair of large bone defects. Abstract : Material–tissue interactions control the long‐term outcomes of bone repair using synthetic bone substitutes. For the first time, specific material–tissue interactions at the bone–implant interface are investigated following implantation of a synthetic scaffold for critical‐sized defect repair in sheep tibia. Focused ion beam scanning electron microscopy, multiphoton microscopy, and histology provide important information that enables predictions of long‐term implant performance.